Multicomponent reactions: A simple and efficient route to heterocyclic phosphonates - Haji, Mohammad (Beilstein Journal of Organic Chemistry, 2016)
Multicomponent reactions (MCRs) are one of the most important processes for the preparation of highly functionalized organic compounds in modern synthetic chemistry. As shown in this review, they play an important role in organophosphorus chemistry where phosphorus reagents are used as substrates for the synthesis of a wide range of phosphorylated heterocycles. In this article, an overview about multicomponent reactions used for the synthesis of heterocyclic compounds bearing a phosphonate group on the ring is given.
Keywords: multicomponent reactions; organophosphorus chemistry; phosphorus reagents; phosphorylated heterocycles